Adherence to HIV Treatment and Care Among Previously Homeless Jail Detainees. - Chen, Nadine E; Meyer, Jaimie P; Avery, Ann K; Draine, Jeffrey; Flanigan, Timothy P; Lincoln, Thomas; Spaulding, Anne C; Springer, Sandra A; Altice, Frederick L (AIDS and behavior, 2011)
HIV-infected persons entering the criminal justice system (CJS) often experience suboptimal healthcare system engagement and social instability, including homelessness. We evaluated surveys from a multisite study of 743 HIV-infected jail detainees prescribed or eligible for antiretroviral therapy (ART) to understand correlates of healthcare engagement prior to incarceration, focusing on differences by housing status. Dependent variables of healthcare engagement were: (1) having an HIV provider, (2) taking ART, and (3) being adherent (≥95% of prescribed doses) to ART during the week before incarceration. Homeless subjects, compared to their housed counterparts, were significantly less likely to be engaged in healthcare using any measure. Despite Ryan White funding availability, insurance coverage remains insufficient among those entering jails, and having health insurance was the most significant factor correlated with having an HIV provider and taking ART. Individuals interfacing with the CJS, especially those unstably housed, need innovative interventions to facilitate healthcare access and retention.